Using SAR to monitor tropical forest in the Amazon - Asociación para la Conservación de la Cuenca Amazónica (Asociación para la Conservación de la Cuenca Amazónica - ACCA, 2019)
Using SAR to monitor tropical forest in the Amazon. Workshop Lima, Peru. November 2019